2019
DOI: 10.1016/j.ygyno.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficiency of comprehensive hysteroscopic evaluation and lesion resection combined with progestin therapy in young women with endometrial atypical hyperplasia and endometrial cancer

Abstract: Mean treatment duration to achieve CR was 6.7 ± 0.3 months, using progestin therapy combined with hysteroscopic evaluation. • Endometrial lesion size ≤2 cm correlated with a shorter treatment period to achieve CR. • Comprehensive hysteroscopic evaluation seems to be effective for EAH and EEC patients who wish to preserve fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 30 publications
(38 reference statements)
2
57
0
1
Order By: Relevance
“…Pregnancy rates in these studies among those who attempted conception, including through assisted reproductive technology (ART), ranged from 25% to 66%, suggesting the potential for superior outcomes compared to hormone treatment alone. Recent studies have confirmed these findings, reporting complete response rates in women with stage 1A EC of 89% to 97% following hysteroscopic fertility-sparing treatment, and pregnancy rates of over 45% among women who attempted conception [ 78 , 79 ]. Concerns have been raised about possible negative consequences of hysteroscopy due to EC cells spreading into the peritoneal cavity and the likelihood of adverse pregnancy outcomes due to mechanical damage to the basal layer of the endometrium causing Asherman’s syndrome and a risk of placenta accreta [ 80 ].…”
Section: Fertility-sparing Managementmentioning
confidence: 86%
“…Pregnancy rates in these studies among those who attempted conception, including through assisted reproductive technology (ART), ranged from 25% to 66%, suggesting the potential for superior outcomes compared to hormone treatment alone. Recent studies have confirmed these findings, reporting complete response rates in women with stage 1A EC of 89% to 97% following hysteroscopic fertility-sparing treatment, and pregnancy rates of over 45% among women who attempted conception [ 78 , 79 ]. Concerns have been raised about possible negative consequences of hysteroscopy due to EC cells spreading into the peritoneal cavity and the likelihood of adverse pregnancy outcomes due to mechanical damage to the basal layer of the endometrium causing Asherman’s syndrome and a risk of placenta accreta [ 80 ].…”
Section: Fertility-sparing Managementmentioning
confidence: 86%
“…Yang et al . reported a large number of cases of comprehensive hysteroscopic evaluation and lesion resections combined with progestin therapy in young women with AEH and EC . Women with EC treated by hysteroscopic resectioning combined with progestin therapy had a regression, recurrence and pregnancy rate of 97.3%, 11.1% and 37.5%, respectively.…”
Section: Current Methods Used In Fertility‐sparing Treatment Of Endommentioning
confidence: 99%
“…Work-up for fertility preservation treatments Fertility-sparing treatments should be considered in patients with atypical hyperplasia/endometrioid intraepithelial neoplasia (AH/EIN) or grade 1 endometrioid carcinoma without myometrial invasion [262][263][264][265][266][267][268]. There are very few published data on patients with stage IA grade 2 endometrioid carcinoma without myometrial invasion who received fertility sparing treatment with combined oral medroxyprogesterone acetate/levonorgestrel intrauterine system [269].…”
Section: Fertility Preservationmentioning
confidence: 99%
“…So far, there are no available randomized controlled trials comparing different methods of conservative treatment in women with AH/EIN or presumed stage IA grade 1 endometrioid carcinoma. Existing data suggest that patients who received hysteroscopic resection followed by progestin therapy achieve the highest complete remission rate as compared with other existing fertilitypreserving treatments [262][263][264][265][266][267][268][277][278][279][280][281][282][283][284][285][286][287][288][289][290][291][292][293][294]. Intrauterine progestin therapy such as levonorgestrel-releasing intrauterine system combined with gonadotropin-release hormone receptor agonist/progestin have a satisfactory pregnancy rate and low recurrence rate.…”
Section: Management and Follow-up For Fertility Preservationmentioning
confidence: 99%